Distance Technologies of the Creative Abilities Development as the Component of the Process of Formation Soft Skills - Alieksieieva, Hanna; Kravchenko, Nataliia; Horbatiuk, Larysa; Zhyhir, Viktoriia; Chernieha, Olena (London : B P International, 2022)
The work is dedicated to the problem of developing the creative abilities of students as a component of soft skills. The model of formation of the creative professional potential of future specialists is proposed. To describe the conceptual model, the methodology of functional modeling within the graphical notation IDEF0 is used. For the construction of creative abilities during distance learning, it is advisable to use systems of education management, to use cloudtechnologies, systems of videoconferences’ organization, and messengers. The experience of the formation of the creative professional potential of students of Berdiansk State Pedagogical University with the help of distance learning is described.